Decomposition formulas for some quadruple hypergeometric series - Berdyshev, A.S.; Hasanov, A.; Ryskan, A.R. (Bulletin of the Karaganda University. Mathematics Series, 2020)
In the present work, the authors obtained operator identities and decomposition formulas for second order Gauss hypergeometric series of four variables into products containing simpler hypergeometric functions. A Choi–Hasanov method based on the inverse pairs of symbolic operators is used. The obtained expansion formulas for the hypergeometric functions of four variables will allow us to study the properties of these functions. These decompositions are used to study the solvability of boundary value problems for degenerate multidimensional partial differential equations.